Literature for little bodhisattvas: making Buddhist families in modern Taiwan - Heller, Natasha (Contemporary Buddhism, 2025)
"In Literature for little bodhisattvas, Natasha Heller makes two key interventions: first, she argues that picturebooks are a new genre of Buddhist writing, and second, she calls attention to an emergent family Buddhism in Taiwan that fashions children as religious subjects through shared attention with adult readers. Surveying Taiwanese Buddhism from the ground up, Heller explores the changing family dynamics that have made children into a crucial audience for Buddhist education and the home a key site for Buddhist cultivation. By taking picturebooks seriously as part of the Buddhist textual tradition, Heller demonstrates their engagement with canonical sources alongside innovations for modern audiences. Close readings analyzing both text and image trace narrative themes about Buddhist figures, and connect representations of Buddhas and Bodhisattvas to a visual culture where new values such as cuteness are articulated. Heller shows that picturebooks have become an integral part of a contemporary Buddhist education that equips children with strategies to interpret everyday life in Buddhist ways and provides religious models for action in the modern world. Literature for little bodhisattvas is a pathbreaking work revealing how contemporary picturebooks reframe Buddhism and offer fresh perspectives on its teachings and ideals of family for both children and adults"-- Provided by publisher